Menakar Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Dalam Perspektif Hukum Profetik - Maslul, Syaifullahil (Fakultas Hukum Universitas Islam Indonesia, 2025)
The controversies surrounding the Constitutional Court Decision Number 90/PUU-XXI/2023 have attracted public attention. The a quo decision is related to the judicial review of Article 169 letter q of the Election Law. This study questions the a quo decision which grants the applicant's request. This study uses the perspective of Prophetic Law. The Prophetic Law perspective consists of humanity, liberation and transcendence. The results of the study show: The Constitutional Court Decision Number 90/PUU-XXI/2023 does not represent the values ​​in Prophetic Law. The a quo decision loses its humanization value when it only places individual interests above public interests. In addition, the Constitutional Justices who are agents of liberation have failed by radically altering the Decision in a flash. When the values ​​of humanity and liberation are ignored, the dimension of transcendence is also lost. This decision does not meet the ethics, conscience, and divine values ​​the basis for making decisions, even though prophetic law demands spiritual awareness in the law enforcement process.Keywords: Humanity, Prophetic Law, Liberation, Constitutional Court Decision, Transcendence AbstrakProblematika Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 menyita perhatian publik. Putusan a quo berkaitan dengan pengujian Pasal 169 huruf q UU Pemilu. Penelitian ini mempermasalahkan Putusan a quo yang mengabulkan permohonan pemohon. Penelitian ini menggunakan sudut pandang Hukum Profetik. Pandangan Hukum Profetik terdiri dari humanisasi, liberasi dan transendensi. Hasil dari penelitian menunjukkan: Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 tidak merepresentasikan nilai-nilai dalam Hukum Profetik. Putusan a quo kehilangan nilai humanisasinya ketika hanya menempatkan kepentingan perseorangan di atas kepentingan publik. Selain daripada itu, Hakim Konstitusi yang merupakan agen liberasi/pembebasan telah gagal dengan berubahnya Putusan secara radikal hanya dengan hitungan waktu